(untitled) (AmeriQuests, 2020)
The landscape of American Zionism shifted slowly and significantly over the course of the early to mid 20th century, culminating in the creation of the State of Israel in 1948. In that tumultuous period of history, American Zionism was not one single traceable ideology, but a great mass of intersecting and opposing ideologies, formed by American Jews’ desire to assimilate and their response to ongoing and pervasive anti-Semitism in the United States and Europe. One particular student Zionist organization, known as Avukah, cultivated its own Zionist ideology and attempted to spread its message to universities across the country. However, as American Zionism transformed and took root in mainstream American Jewish society, Avukah struggled and ultimately failed to instill its Zionist ideology into the mainstream. Avukah’s strict adherence to a singular, yet ultimately unclear Zionist ideology and its inability to adapt to the shifting tides of American Zionism provide a unique lens into the world of early American Zionist culture and the limitations of organizations founded on strict adherence to ideology. The study of Avukah’s rise and fall through the prism of the Avukah chapter at Temple University offers a close examination and microcosm of the limitations of Avukah’s Zionist ideology in the face of American Zionism’s period of great change.